Irony's edge : the theory and politics of irony - Hutcheon, Linda, 1947- (Routledge, 1995)
The edge of irony, says Linda Hutcheon, is always a social and political edge. Irony depends upon interpretation; it happens in the tricky, unpredictable space between expression and understanding. Irony's Edge is a fascinating, compulsively readable study of the myriad forms and the effects of irony. It sets out, for the first time, a sustained, clear analysis of the theory and the political contexts of irony, using a wide range of references from contemporary culture. Examples extend from Madonna to Wagner, from a clever quip in conversation to a contentious exhibition in a museum. Irony's Edge outlines and then challenges all the major existing theories of irony, providing the most comprehensive and critically challengin theory of irony to date.